Dehydrocorydaline Protects Against Sepsis-Induced Myocardial Injury Through Modulating the TRAF6/NF-κB Pathway - Zhang, Li; Jiang, Hong; Zhang, Ping (Frontiers in Pharmacology, 2021)
We aim to investigate the effect and mechanism of dehydrocorydaline (Deh), an alkaloidal component isolated from Rhizoma corydalis, in the treatment of sepsis-mediated myocardial injury. Lipopolysaccharide (LPS) was taken to construct an in-vitro sepsis-myocardial injury models H9C2 cardiomyocytes. The in-vivo model of sepsis in C57BL/6 mice was induced by intraperitoneal injection of Escherichia coli (E. coli). The in-vitro and in-vivo models were treated with Deh in different concentrations, respectively. Hematoxylin-eosin (HE) staining, Masson staining, and immunohistochemistry (IHC) staining were taken to evaluate the histopathological changes of the heart. ELISA was applied to evaluate the levels of inflammatory factors, including IL-6, IL-1β, TNFα, IFNγ， and oxidized factors SOD, GSH-PX in the plasma or culture medium. Western blot was used to measure the expressions of Bax, Bcl2, Caspase3, iNOS, Nrf2, HO-1, TRAF6, NF-κB in heart tissues and cells. The viability of H9C2 cardiomyocytes was detected by the CCK8 method and BrdU assay. The ROS level in the H9C2 cardiomyocytes were determined using immunofluorescence. As a result, Deh treatment improved the survival of sepsis mice, reduced TUNEL-labeled apoptosis of cardiomyocytes. In vitro, Deh enhanced the viability of LPS-induced H9C2 cardiomyocytes and inhibited cell apoptosis. Additionally, Deh showed significant anti-inflammatory and anti-oxidative stress functions via decreasing IL-1β, IL-6, TNFα, and IFNγ levels, mitigating ROS level, up-regulating Nrf2/HO-1, SOD, and GSH-PX expressions dose-dependently. Mechanistically, Deh inhibited TRAF6 expression and the phosphorylation of NF-κB p65. The intervention with a specific inhibitor of TRAF6 (C25-140) or NF-κB inhibitor (BAY 11-7082) markedly repressed the protective effects mediated by Deh. In conclusion, Deh restrains sepsis-induced cardiomyocyte injury by inhibiting the TRAF6/NF-κB pathway.